Singular surface for non-ideal two-phase modified Chaplygin flow consisting of source term. (March 2023) - Sharma, Deepika; Singh, Randheer
Abstract: In this manuscript, a system of partial differential equations (PDEs) outlining one-dimensional isentropic two-phase flow model consisting of a non-constant source term with non-ideal modified Chaplygin gas is derived. The model is reduced to an equivalent system of ordinary differential equations (ODEs) via Lie group scheme. The transport equation for the singular surface is derived using the compatibility conditions and solved numerically by coupling with the system of ODEs. Further, the effects of inclination of the flow and non-idealness on the amplitude of steepened wave (or singular surface) are investigated. Highlights: A real two-phase flow model of modified Chaplygin gas is derived. A new modified Chaplygin equation of state for non-ideal compressible two-phase flow is introduced. Lie group scheme is employed to determine the solution. The transport equation for the singular surface is derived. The effects of inclination of the flow and non-idealness on steepened wave are investigated.